2020
DOI: 10.1007/s11244-020-01352-6
|View full text |Cite|
|
Sign up to set email alerts
|

Passive NO Adsorption on Hydrothermally Aged Pd-Based Small-Pore Zeolites

Abstract: Pd-based small-pore zeolites with different framework structures (AEI, CHA and RTH) were synthesized by a facile incipient wetness impregnation method. The zeolites were utilized as low-temperature passive NO x adsorbers (PNA) for NO x storage before and after hydrothermal aging. It was found that 1 wt% Pd/AEI showed better PNA behavior than the 1 wt% Pd/ CHA and Pd/RTH samples, regardless of hydrothermal aging at 750 and 800 ℃. The AEI zeolite has a three-dimensional but tortuous pore channel structure, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…However, Khivantsev et al [16] found that, Pd 2+ cations were agglomerated to PdO in the Pd/SSZ-13 after hydrothermal aging at 750 ºC, where all the Pd stay as Pd 2+ ions, resulting in a minor decline of NO storage capacity. Theis et al [15] and Shan et al [20] also observed the deactivation of Pd/CHA catalysts after aging at 800 ºC. Recently, Wang et al [21] compared the hydrothermal stability of Pd/SSZ-13 and Pd/LTA catalysts with similar Si/Al ratio (15).…”
Section: Introductionmentioning
confidence: 98%
“…However, Khivantsev et al [16] found that, Pd 2+ cations were agglomerated to PdO in the Pd/SSZ-13 after hydrothermal aging at 750 ºC, where all the Pd stay as Pd 2+ ions, resulting in a minor decline of NO storage capacity. Theis et al [15] and Shan et al [20] also observed the deactivation of Pd/CHA catalysts after aging at 800 ºC. Recently, Wang et al [21] compared the hydrothermal stability of Pd/SSZ-13 and Pd/LTA catalysts with similar Si/Al ratio (15).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Pd-exchanged zeolites were proposed as promising materials for this technology. , Highly dispersed Pd ions at exchange sites of a zeolite have been suggested as active sites for NO x storage at low temperatures . Subsequently, many research groups have studied NO x adsorption/desorption properties over Pd zeolites. Small-pore Pd-SSZ-13 with chabazite (CHA) topology showed advantageous NO x release temperatures and higher hydrothermal stability compared to medium- and large-pore Pd zeolites. , …”
Section: Introductionmentioning
confidence: 99%
“…74 He et al reported that the Pd-based SSZ-39 zeolite with excellent high temperature hydrothermal aging feature could be very efficient in low-temperature passive NO x adsorbers (PNAs) for NO x storage and methane combustion processes. 75,76 Moreover, Ipek et al reported that the Cu( i )-exchanged SSZ-39 zeolite was found to have excellent hydrogen storage capacity, which was comparable to the highest adsorption capacity values reported on metal–organic frameworks. 77 In addition, Yokoi et al first showed the performance of the SSZ-39 zeolite in the catalytic conversion of the propene to butene (PTB) reaction.…”
Section: Application Of the Ssz-39 Zeolitementioning
confidence: 81%
“…Besides the two above mentioned catalytic applications, the SSZ-39 zeolite could also be applied to several other applications. 56,[74][75][76][77][78][79][80][81][82] Tian et al reported that the SSZ-39 zeolite doped with Eu 2+ cations had strong tuneable blue emission and good thermal stability, which suggested a potential application of the Eu-SSZ-39 zeolite in light-emitting diode (LED) phosphors (Fig. 8).…”
Section: Other Applicationsmentioning
confidence: 99%